2013
DOI: 10.1101/gr.141614.112
|View full text |Cite
|
Sign up to set email alerts
|

Efficient neocentromere formation is suppressed by gene conversion to maintain centromere function at native physical chromosomal loci in Candida albicans

Abstract: CENPA/Cse4 assembles centromeric chromatin on diverse DNA. CENPA chromatin is epigenetically propagated on unique and different centromere DNA sequences in a pathogenic yeast Candida albicans. Formation of neocentromeres on DNA, nonhomologous to native centromeres, indicates a role of non-DNA sequence determinants in CENPA deposition. Neocentromeres have been shown to form at multiple loci in C. albicans when a native centromere was deleted. However, the process of site selection for CENPA deposition on native… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
114
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(121 citation statements)
references
References 58 publications
6
114
1
Order By: Relevance
“…The conditions for de novo centromere formation remain unclear (26). Recent research revealed that many de novo centromeres prefer to form near native centromeric regions or in the heterochromatic regions, such as the pericentromere and telomere (27,28). There are also de novo centromeres in human formed far from native centromeres (20).…”
Section: Significancementioning
confidence: 99%
“…The conditions for de novo centromere formation remain unclear (26). Recent research revealed that many de novo centromeres prefer to form near native centromeric regions or in the heterochromatic regions, such as the pericentromere and telomere (27,28). There are also de novo centromeres in human formed far from native centromeres (20).…”
Section: Significancementioning
confidence: 99%
“…In C. albicans (yeast) and Gallus gallus (chicken) DT40 cells, new centromeres were found in several positions, most frequently close to the original centromere (141, 154). It is thought that low levels of CENP-A in regions flanking the centromere may seed these new centromeres.…”
Section: Introductionmentioning
confidence: 99%
“…The absence of satellite sequences in neocentromeres is indicative of their nonessential centromere function. The conclusion from a phylogenetically broad spectrum of plants and animals indicates that there are neocentromere-favorable and -unfavorable sites (154, 161). Unlike the kinetochore, with its readily identifiable essential proteins, it is difficult (outside of budding yeast) to identify genetic sequences or modifications that definitively mark or exclude centromere formation.…”
Section: Introductionmentioning
confidence: 99%
“…The hybrid condition did not reposition the centromeres, even though neocentromeres have a high propensity to be formed in C. albicans chromosomes (34). ChIP analysis revealed that the centromere location of chromosome 4 changed between two C. dubliniensis strains, Cd36 (19) and CdUM4b.…”
Section: Discussionmentioning
confidence: 95%